2020
DOI: 10.1016/j.metop.2020.100025
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical decrease in cardiac autonomic and diastolic function in patients with metabolic disorders: HSCAA study

Abstract: Heart failure due to decreased diastolic function, HFpEF, is a growing health concern with rising prevalence. We examined subclinical cardiac autonomic and diastolic functions in 605 patients with metabolic diseases classified as pre-heart failure. Presence of glucose intolerance or diabetes, or visceral adiposity was significantly associated with reduced cardiac autonomic and diastolic functions. Higher autonomic functions were significantly associated with a parameter of better cardiac diastolic function (E/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…LV diastolic dysfunction is an important cause of HFpEF in individuals with diabetes and epidemiologic studies have demonstrated the presence of diastolic dysfunction in type 2 diabetes patients [15,16]. In our recent study, diabetic patients exhibited higher E/e' as compared to those with either normal or impaired glucose tolerance [11]. Among the available parameters of LV diastolic function, E/e′ determined with a non-invasive approach has long been used to assess LV lling pressure in various patient populations [17].…”
Section: Diabetes and Cardiac Diastolic Dysfunctionmentioning
confidence: 63%
See 1 more Smart Citation
“…LV diastolic dysfunction is an important cause of HFpEF in individuals with diabetes and epidemiologic studies have demonstrated the presence of diastolic dysfunction in type 2 diabetes patients [15,16]. In our recent study, diabetic patients exhibited higher E/e' as compared to those with either normal or impaired glucose tolerance [11]. Among the available parameters of LV diastolic function, E/e′ determined with a non-invasive approach has long been used to assess LV lling pressure in various patient populations [17].…”
Section: Diabetes and Cardiac Diastolic Dysfunctionmentioning
confidence: 63%
“…LV function was evaluated by echocardiography as previously described [11]. Examinations were repeated every 1-3 years to determine changes in LV function.…”
Section: Assessment Of LV Diastolic Functionmentioning
confidence: 99%
“…HRV using an Active Tracer device (AC-301A ® , Arm Electronics, Tokyo, Japan) was used for noninvasive determination of cardiac modulation based on autonomic balance, as previously described 14 , 22 24 . The final 24-h series of data from the 48-h recording was analyzed using a MemCalc Chiram 3 system, version 2.0 (Suwa Trust, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…2351). This cross-sectional study was conducted as part of the HSCAA Study, which was instituted to examine the impacts of sleep and autonomic imbalance on metabolic, renal, and cardiovascular events [25] , [26] . Patients with 1 or more cardiovascular risk factors, including obesity, smoking, presence of cardiovascular event history, hypertension, dyslipidemia, diabetes mellitus, and chronic kidney disease, and being treated at the Division of Diabetes, Endocrinology and Metabolism of Hyogo Medical College Hospital (Hyogo, Japan) were registered.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze cardiac autonomic nervous activity, heart rate variability (HRV) was measured in a noninvasive manner with an Active Tracer device (AC-301A®, Arm Electronics, Tokyo, Japan) and a MemCalc Chiram 3 system, version 2.0 (Suwa Trust, Tokyo, Japan), as previously described [25] , [26] , [39] , [40] . According to the recommendations for clinical use of HRV [ 22 ], the standard deviation of the NN(RR) interval (SDNN) was calculated.…”
Section: Methodsmentioning
confidence: 99%